2007
DOI: 10.1149/1.2789296
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Temperature Proton Conduction in Al[sup 3+]-Doped SnP[sub 2]O[sub 7]

Abstract: Al3+ -doped SnnormalP2normalO7 proton conductors were prepared by controlling the initial composition of the reactants [ SnnormalO2 , Al(OH)3 , and normalH3PnormalO4 ]. normalSn1−xnormalAlxnormalPynormalOz with y<2 displayed conductivities approximately two orders of magnitude lower than normalSn1−xnormalAlxnormalP2normalO7 , while those of normalSn1−xnormalAlxnormalPynormalOz with y2 exhibited conductivities at a maximum of 1.99 times higher. However, because the conductivity values of normalSn1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 20 publications
(33 reference statements)
5
87
2
1
Order By: Relevance
“…29 showed a conductivity of several orders of magnitude lower. It was suggested that the excess phosphoric acid in the preparation promoted the formation of a secondary amorphous phase in grain boundaries, which was considered to provide additional pathways for proton transport, 30 and therefore significantly enhance the conductivity.…”
Section: Electromotive Force (Emf) and Open Circuit Voltage (Ocv) Meamentioning
confidence: 99%
See 1 more Smart Citation
“…29 showed a conductivity of several orders of magnitude lower. It was suggested that the excess phosphoric acid in the preparation promoted the formation of a secondary amorphous phase in grain boundaries, which was considered to provide additional pathways for proton transport, 30 and therefore significantly enhance the conductivity.…”
Section: Electromotive Force (Emf) and Open Circuit Voltage (Ocv) Meamentioning
confidence: 99%
“…It can be seen from the figure that the obtained EMF was very close to the theoretical values calculated from the Nernst equation. The ratio of the measured EMF to the theoretical value was assumed to be the proton transference number 30,34 and was found to be between 0.97 and 0.98. This indicated the protonic nature of the ionic conductivity of the niobium phosphates.…”
Section: Emf and Ocv Measurementsmentioning
confidence: 99%
“…In recent years, considerable effort has been made to develop novel solid proton conductors for fuel cells, based on pyrophosphates of tetravalent metals [7][8][9][10][11] that operate at 200-300°C. Various MP 2 O 7 (M = Si, Zr, Ti, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…13) Interestingly, the proton conductivity of SnP 2 O 7 could be increased to ³10 ¹1 S cm ¹1 by the substitution of low valency cations, including In 3+ , 18) Al 3+ , 19) Mg 2+ , 20) Sb 3+ , 21) Sc 3+ , 22) and Ga 3+ 23) for part of the Sn 4+ cations. This conductivity value is sufficiently high for good performance of electrochemical devices.…”
Section: ¹1mentioning
confidence: 99%